The equation of the straight line joining the point $\left( a,b \right)$ to the point of
intersection of the lines $\dfrac{x}{a}+\dfrac{y}{b}=1$ and $\dfrac{x}{b}+\dfrac{y}{a}=1$ is
(a) ${{a}^{2}}y-{{b}^{2}}x=ab\left( a-b \right)$
(b) ${{a}^{2}}x+{{b}^{2}}y=ab\left( a+b \right)$
(c) ${{a}^{2}}y+{{b}^{2}}x=ab$
(d) ${{a}^{2}}x+{{b}^{2}}y=ab\left( a-b \right)$
Answer
Verified
511.8k+ views
Hint: Solve the 2 line equations to find the point of intersection. Substitute these intersection points along with the given coordinate points back into the line equations.
The two equations given in the question are,
$\dfrac{x}{a}+\dfrac{y}{b}=1$ and $\dfrac{x}{b}+\dfrac{y}{a}=1$
The given equations can be rearranged as,
$\dfrac{x}{a}+\dfrac{y}{b}-1=0$ and $\dfrac{x}{b}+\dfrac{y}{a}-1=0$
The point of intersection of these two lines can be obtained by solving the equations and finding the values of \[x\] and \[y\]. Subtracting the equations,
\[\left( \dfrac{x}{a}+\dfrac{y}{b}-1 \right)-\left( \dfrac{x}{b}+\dfrac{y}{a}-1 \right)=0\]
Taking similar terms together,
\[\left( \dfrac{x}{a}-\dfrac{x}{b} \right)+\left( \dfrac{y}{b}-\dfrac{y}{a} \right)+(-1+1)=0\]
Taking out the common terms,
\[\begin{align}
& x\left( \dfrac{1}{a}-\dfrac{1}{b} \right)+y\left( \dfrac{1}{b}-\dfrac{1}{a} \right)=0 \\
& x\left( \dfrac{1}{a}-\dfrac{1}{b} \right)-y\left( \dfrac{1}{a}-\dfrac{1}{b} \right)=0 \\
\end{align}\]
Again, taking out the common term, we get,
\[\begin{align}
& \left( x-y \right)\left( \dfrac{1}{a}-\dfrac{1}{b} \right)=0 \\
& \left( x-y \right)=0 \\
& x=y \\
\end{align}\]
Now we can substitute \[x=y\] in one of the equations of the lines, say $\dfrac{x}{a}+\dfrac{y}{b}-1=0$,
$\begin{align}
& \dfrac{y}{a}+\dfrac{y}{b}-1=0 \\
& \Rightarrow y\left( \dfrac{1}{a}+\dfrac{1}{b} \right)-1=0 \\
& \Rightarrow y\left( \dfrac{1}{a}+\dfrac{1}{b} \right)=1 \\
\end{align}$
Taking the LCM,
$\begin{align}
& \Rightarrow y\left( \dfrac{b+a}{ab} \right)=1 \\
& \Rightarrow y=\dfrac{1}{\left( \dfrac{b+a}{ab} \right)} \\
& \Rightarrow y=\left( \dfrac{ab}{b+a} \right) \\
& \Rightarrow y=\left( \dfrac{ab}{a+b} \right) \\
\end{align}$
Since \[x=y\], we get the coordinates as$x=y=\left( \dfrac{ab}{a+b} \right)$. Therefore, we can write the coordinates of the point of intersection of the lines $\dfrac{x}{a}+\dfrac{y}{b}=1$ and $\dfrac{x}{b}+\dfrac{y}{a}=1$ as $\left[ \left( \dfrac{ab}{a+b} \right),\left( \dfrac{ab}{a+b} \right) \right]$.
The equation of a line passing through two points \[({{x}_{1}},{{y}_{1}})\] and \[({{x}_{2}},{{y}_{2}})\] is given by,
\[\begin{align}
& y-{{y}_{1}}=m(x-{{x}_{1}}) \\
& \Rightarrow y-{{y}_{1}}=\dfrac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}\times (x-{{x}_{1}}) \\
\end{align}\]
So, the equation of the straight line joining the point $\left( a,b \right)$ and $\left[ \left( \dfrac{ab}{a+b} \right),\left( \dfrac{ab}{a+b} \right) \right]$ can be found as,
\[y-b=\left( \dfrac{\dfrac{ab}{a+b}-b}{\dfrac{ab}{a+b}-a} \right)\left( x-a \right)\]
Taking the LCM of the terms in the numerator and denominator,
\[y-b=\left( \dfrac{\dfrac{ab-b(a+b)}{a+b}}{\dfrac{ab-a(a+b)}{a+b}} \right)\left( x-a \right)\]
Opening the brackets and simplifying the terms,
\[\begin{align}
& y-b=\left( \dfrac{\dfrac{ab-ba-{{b}^{2}})}{a+b}}{\dfrac{ab-{{a}^{2}}-ab)}{a+b}} \right)\left( x-a \right) \\
& y-b=\left( \dfrac{\dfrac{-{{b}^{2}}}{a+b}}{\dfrac{-{{a}^{2}}}{a+b}} \right)\left( x-a \right) \\
& y-b=\left( \dfrac{{{b}^{2}}}{{{a}^{2}}} \right)\left( x-a \right) \\
& {{a}^{2}}(y-b)={{b}^{2}}(x-a) \\
& {{a}^{2}}y-{{a}^{2}}b={{b}^{2}}x-{{b}^{2}}a \\
& {{b}^{2}}x-{{a}^{2}}y={{b}^{2}}a-{{a}^{2}}b \\
& {{b}^{2}}x-{{a}^{2}}y=ab(b-a) \\
\end{align}\]
Looking at the given options, we can rewrite the obtained equation as
\[\begin{align}
& -{{b}^{2}}x+{{a}^{2}}y=-ab(b-a) \\
& {{a}^{2}}y-{{b}^{2}}x=ab(a-b) \\
\end{align}\]
Therefore, we get option (a) as the correct answer.
Note: The equation of a straight line passing through the point of intersection of two lines, say A and B can be written as \[A+\lambda B=0\]. Therefore, the equation of the straight line passing through the point of intersection of the given lines $\dfrac{x}{a}+\dfrac{y}{b}-1=0$ and $\dfrac{x}{b}+\dfrac{y}{a}-1=0$ can be written as, $\left( \dfrac{x}{a}+\dfrac{y}{b}-1 \right)+\lambda \left( \dfrac{x}{b}+\dfrac{y}{a}-1 \right)=0$. Since the required straight line passes through point $\left( a,b \right)$, we can substitute the coordinates in the above equation and find the value of $\lambda $. This method is lengthy as it has complex terms.
The two equations given in the question are,
$\dfrac{x}{a}+\dfrac{y}{b}=1$ and $\dfrac{x}{b}+\dfrac{y}{a}=1$
The given equations can be rearranged as,
$\dfrac{x}{a}+\dfrac{y}{b}-1=0$ and $\dfrac{x}{b}+\dfrac{y}{a}-1=0$
The point of intersection of these two lines can be obtained by solving the equations and finding the values of \[x\] and \[y\]. Subtracting the equations,
\[\left( \dfrac{x}{a}+\dfrac{y}{b}-1 \right)-\left( \dfrac{x}{b}+\dfrac{y}{a}-1 \right)=0\]
Taking similar terms together,
\[\left( \dfrac{x}{a}-\dfrac{x}{b} \right)+\left( \dfrac{y}{b}-\dfrac{y}{a} \right)+(-1+1)=0\]
Taking out the common terms,
\[\begin{align}
& x\left( \dfrac{1}{a}-\dfrac{1}{b} \right)+y\left( \dfrac{1}{b}-\dfrac{1}{a} \right)=0 \\
& x\left( \dfrac{1}{a}-\dfrac{1}{b} \right)-y\left( \dfrac{1}{a}-\dfrac{1}{b} \right)=0 \\
\end{align}\]
Again, taking out the common term, we get,
\[\begin{align}
& \left( x-y \right)\left( \dfrac{1}{a}-\dfrac{1}{b} \right)=0 \\
& \left( x-y \right)=0 \\
& x=y \\
\end{align}\]
Now we can substitute \[x=y\] in one of the equations of the lines, say $\dfrac{x}{a}+\dfrac{y}{b}-1=0$,
$\begin{align}
& \dfrac{y}{a}+\dfrac{y}{b}-1=0 \\
& \Rightarrow y\left( \dfrac{1}{a}+\dfrac{1}{b} \right)-1=0 \\
& \Rightarrow y\left( \dfrac{1}{a}+\dfrac{1}{b} \right)=1 \\
\end{align}$
Taking the LCM,
$\begin{align}
& \Rightarrow y\left( \dfrac{b+a}{ab} \right)=1 \\
& \Rightarrow y=\dfrac{1}{\left( \dfrac{b+a}{ab} \right)} \\
& \Rightarrow y=\left( \dfrac{ab}{b+a} \right) \\
& \Rightarrow y=\left( \dfrac{ab}{a+b} \right) \\
\end{align}$
Since \[x=y\], we get the coordinates as$x=y=\left( \dfrac{ab}{a+b} \right)$. Therefore, we can write the coordinates of the point of intersection of the lines $\dfrac{x}{a}+\dfrac{y}{b}=1$ and $\dfrac{x}{b}+\dfrac{y}{a}=1$ as $\left[ \left( \dfrac{ab}{a+b} \right),\left( \dfrac{ab}{a+b} \right) \right]$.
The equation of a line passing through two points \[({{x}_{1}},{{y}_{1}})\] and \[({{x}_{2}},{{y}_{2}})\] is given by,
\[\begin{align}
& y-{{y}_{1}}=m(x-{{x}_{1}}) \\
& \Rightarrow y-{{y}_{1}}=\dfrac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}\times (x-{{x}_{1}}) \\
\end{align}\]
So, the equation of the straight line joining the point $\left( a,b \right)$ and $\left[ \left( \dfrac{ab}{a+b} \right),\left( \dfrac{ab}{a+b} \right) \right]$ can be found as,
\[y-b=\left( \dfrac{\dfrac{ab}{a+b}-b}{\dfrac{ab}{a+b}-a} \right)\left( x-a \right)\]
Taking the LCM of the terms in the numerator and denominator,
\[y-b=\left( \dfrac{\dfrac{ab-b(a+b)}{a+b}}{\dfrac{ab-a(a+b)}{a+b}} \right)\left( x-a \right)\]
Opening the brackets and simplifying the terms,
\[\begin{align}
& y-b=\left( \dfrac{\dfrac{ab-ba-{{b}^{2}})}{a+b}}{\dfrac{ab-{{a}^{2}}-ab)}{a+b}} \right)\left( x-a \right) \\
& y-b=\left( \dfrac{\dfrac{-{{b}^{2}}}{a+b}}{\dfrac{-{{a}^{2}}}{a+b}} \right)\left( x-a \right) \\
& y-b=\left( \dfrac{{{b}^{2}}}{{{a}^{2}}} \right)\left( x-a \right) \\
& {{a}^{2}}(y-b)={{b}^{2}}(x-a) \\
& {{a}^{2}}y-{{a}^{2}}b={{b}^{2}}x-{{b}^{2}}a \\
& {{b}^{2}}x-{{a}^{2}}y={{b}^{2}}a-{{a}^{2}}b \\
& {{b}^{2}}x-{{a}^{2}}y=ab(b-a) \\
\end{align}\]
Looking at the given options, we can rewrite the obtained equation as
\[\begin{align}
& -{{b}^{2}}x+{{a}^{2}}y=-ab(b-a) \\
& {{a}^{2}}y-{{b}^{2}}x=ab(a-b) \\
\end{align}\]
Therefore, we get option (a) as the correct answer.
Note: The equation of a straight line passing through the point of intersection of two lines, say A and B can be written as \[A+\lambda B=0\]. Therefore, the equation of the straight line passing through the point of intersection of the given lines $\dfrac{x}{a}+\dfrac{y}{b}-1=0$ and $\dfrac{x}{b}+\dfrac{y}{a}-1=0$ can be written as, $\left( \dfrac{x}{a}+\dfrac{y}{b}-1 \right)+\lambda \left( \dfrac{x}{b}+\dfrac{y}{a}-1 \right)=0$. Since the required straight line passes through point $\left( a,b \right)$, we can substitute the coordinates in the above equation and find the value of $\lambda $. This method is lengthy as it has complex terms.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
State the laws of reflection of light